2019
DOI: 10.3390/molecules24173109
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Secondary Metabolites from Melicope lunu-ankenda (Rutaceae)

Abstract: Plant natural compounds have great potential as alternative medicines for preventing and treating diseases. Melicope lunu-ankenda is one Melicope species (family Rutaceae), which is widely used in traditional medicine, consumed as a salad and a food seasoning. Consumption of different parts of this plant has been reported to exert different biological activities such as antioxidant and anti-inflammatory qualities, resulting in a protective effect against several health disorders including neurodegenerative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Similarly, in another study, the neuroprotective effect of caffeoylquinic acid (CQA) derivatives was established against H 2 O 2 -induced neurotoxicity in SH-SY5Y cells via inhibition of oxidative stress and activation of antioxidant defence [37]. Caffeic acid is a cinnamic acid, its neuroprotective effect at dose 222 µM was demonstrated in the pheochromocytoma (PC12) cell line against H 2 O 2 -induced cytotoxicity [17]. A further study revealed that caffeic acid at concentrations of 55.5 and 111 µM exerts neuroprotective activity against Aβ-induced neurotoxicity in pheochromocytoma (PC12) cells via impaired tau phosphorylation and phosphorylation of GSK-3β (glycogen synthase kinase-3β), impaired oxidative stress and a decrease in intracellular calcium levels [34].…”
Section: Effect Of 7-geranyloxycinnamic Acid On Sh-sy5y Cell Viabilitmentioning
confidence: 95%
See 3 more Smart Citations
“…Similarly, in another study, the neuroprotective effect of caffeoylquinic acid (CQA) derivatives was established against H 2 O 2 -induced neurotoxicity in SH-SY5Y cells via inhibition of oxidative stress and activation of antioxidant defence [37]. Caffeic acid is a cinnamic acid, its neuroprotective effect at dose 222 µM was demonstrated in the pheochromocytoma (PC12) cell line against H 2 O 2 -induced cytotoxicity [17]. A further study revealed that caffeic acid at concentrations of 55.5 and 111 µM exerts neuroprotective activity against Aβ-induced neurotoxicity in pheochromocytoma (PC12) cells via impaired tau phosphorylation and phosphorylation of GSK-3β (glycogen synthase kinase-3β), impaired oxidative stress and a decrease in intracellular calcium levels [34].…”
Section: Effect Of 7-geranyloxycinnamic Acid On Sh-sy5y Cell Viabilitmentioning
confidence: 95%
“…The M. lunu-ankenda plant is widely used as a medicinal plant to treat diabetes mellitus, hypertension, menstrual disorders, fever, and as a tonic [15]. Hydroxycinnamic acids are secondary metabolites isolated from M. lunu-ankenda leaves and exhibit antioxidant, anti-inflammatory and neuroprotective activities via impaired H 2 O 2 -mediated oxidative damage [17]. Neuronal cells exposed to H 2 O 2 displayed enhanced intracellular defense mechanisms, including a rise in endogenous antioxidants [33].…”
Section: Effect Of 7-geranyloxycinnamic Acid On Sh-sy5y Cell Viabilitmentioning
confidence: 99%
See 2 more Smart Citations
“…These acids are frequently found in a conjugated form, constituting key building blocks of complex polyphenols, such as acylated derivatives of flavonoid glycosides [5], and they have a number of biological roles in plants, from protection against microbes long been explored for their potential therapeutic applications, most of which related to their antioxidant, antimicrobial, and antineoplastic properties [4,[7][8][9][10][11][12][13][14]. The potential of CA-based compounds as therapeutic agents for other conditions, including Alzheimer's Disease [15], other nervous system disorders [16,17], acute pain [18], inflammation [19], diabetes [20,21], viral infections [22], tuberculosis [23][24][25][26], and malaria [26][27][28][29], among others, has also been addressed. Depending on their therapeutic targets, different modes of action seem to be exerted by CA and their derivatives or analogues.…”
Section: Introductionmentioning
confidence: 99%